Decreased Antibiotic Prescription in an Italian Pediatric Population With Nonspecific and Persistent Upper Respiratory Tract Infections by Use of a Point-of-Care White Blood Cell Count, in Addition to Antibiotic Delayed Prescription Strategy - Luigi Cioffi MD; Raffaele Limauro MD; Roberto Sassi MD; Antonio Boccazzi MD; Donatella del Gaizo MD, PhD (SAGE Publishing, 2016)
The aim of this study was to test, in delayed antibiotic strategy, if the usages of a point-of-care leukocyte count would significantly decrease the prescription rate of antibiotics for children with nonspecific upper respiratory tract infections. A prospective clinical trial was performed in 23 primary care pediatric doctors' offices on children with nonspecific upper respiratory tract infection with fever for at least 48 hours. The children were randomized into 2 groups: one using a point-of-care white blood cell (WBC) count as guidance and the other prescribing antibiotics to all children, according to delayed antibiotics prescription strategy. A total of 792 patients participated. In the WBC group (n = 437), 56 patients had WBC >15 000/mm 3 and received antibiotics. At follow-up, an additional 44 children received antibiotics. In the control group (n = 355), antibiotics were prescribed to all children. The reduction of antibiotic usage was 77% between the groups. The decrease in antibiotic usage gave no influence on recovery, complications, or other medical outcome.